2019
DOI: 10.36965/ojakm.2019.7(1)102-126
|View full text |Cite
|
Sign up to set email alerts
|

Value added knowledge by prosumers in Poland and the UK specifically for service process stages

Abstract: The purpose of the paper is to advance research on knowledge sharing by prosumers with enterprises and public organizations by examining and better understanding what knowledge about improving services, prosumers currently share and would like to share in future. The paper verifies a proposed theoretical framework by showing those service knowledge items that prosumers can share with enterprises and public organizations. The reported outcomes result from a survey that yielded responses by 171 prosumers from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In [44], the authors suggested that the Prosumer Groups (ProG) strive to transform traditional customers into productive consumers, improve SG performance, and deliver an economical, logistical, and sustainable advantage. The authors in [45] have reported that the prosumers aim to generate and consume energy and possibly start sharing and spreading the extra power to other customers in the distribution system using edge technologies. To maximize the use of the edge technology, procedures, business models, and growth incentives, it is vital to understand the roles and priorities of consumers in the early stages of smart grid deployment [46].…”
Section: Summary Of Sg Prosumer/energy Tradementioning
confidence: 99%
“…In [44], the authors suggested that the Prosumer Groups (ProG) strive to transform traditional customers into productive consumers, improve SG performance, and deliver an economical, logistical, and sustainable advantage. The authors in [45] have reported that the prosumers aim to generate and consume energy and possibly start sharing and spreading the extra power to other customers in the distribution system using edge technologies. To maximize the use of the edge technology, procedures, business models, and growth incentives, it is vital to understand the roles and priorities of consumers in the early stages of smart grid deployment [46].…”
Section: Summary Of Sg Prosumer/energy Tradementioning
confidence: 99%
“…Future network services may include prosumers to help SGs overcome difficulties and challenges [ 43 ]. Prosumer Groups (ProG) aim to transform traditional customers into productive consumers, increase SG performance, and provide an economical, logistical and sustainability advantage [ 44 ]. In [ 45 ], the authors mentionned that prosumers want to generate and consume energy and share additional power with other customers in the distribution system via edge technology.…”
Section: Preliminaries: Detailed Analysis Of the Literaturementioning
confidence: 99%
“…For example, product performance is regarded in the UK as one of the primary drivers for business success in competitive markets. While other studies examine prosumer engagement for products and services that are already on the market (Piller, 2008), our studies investigate prosumers' willingness to provide feedback on preferences for products and services that are still in the early stages of the product life cycle (Ziemba et al, 2018;Mullins et al, 2019). This is an important difference, as where business is able to assess prosumers primary concerns and subsequently act on this information by changing designs earlier in the process, especially where this feedback pertains to sustainability concerns, it may be understandable that higher priority will ultimately be placed upon these fundamental important design factors that are becoming increasingly influential in determining why a product is bought.…”
Section: Business Processesmentioning
confidence: 99%
“…Engaging prosumers in knowledge sharing relevant to process BP3.0 market and sell services including (S2) pricing strategy were indicated to be of higher priority to Poland prosumers in the future but were not rated at all highly by the UK-based prosumers, and the prosumers of both countries were equally ambivalent about sharing knowledge regarding promotions (S3) (Mullins et al, 2019). However, this to some extent may be related to the older age of the respondents in our studies, as younger generations use social media much more in their knowledge sharing, this may well change in the future in keeping with consumption practices more widely (Belk, 2014).…”
Section: Business Processesmentioning
confidence: 99%